Geographic information system and unmanned aerial vehicles for soil and pastures evaluation - Espinoza, Freddy; Sevilla , Victor; Machado , Diego (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The objective of this review is to present soil and pasture evaluation studies using georeferenced aerial photographs captured by sensors on board drones and analyzed using the Geographic Information System (GIS) to develop strategies for use in the management of pastures and farm potential. The use of intensive grazing systems requires advanced knowledge for efficient management, and smart and precision agriculture represents a strategy to reduce costs. Using GIS and drones, an immediate comprehensive diagnosis is obtained, such as quantification of the degradation of a pasture or farm, distribution of botanical composition, and variability of soil and pasture nutrients to generate fertilization plans by specific area (precision agriculture).